An eight‐month randomized controlled trial on the use of intra‐oral cameras and text messages for gingivitis control among adults - Araújo, M.-R.; Alvarez, M.-J.; Godinho, C. A.; Roberto, M. S. (International Journal of Dental Hygiene, 2019)
Objective: To investigate the effects of using an intra‐oral camera (IOC) during a dental hygiene consultation and mobile text messages (TM) between appointments on clinical, behavioural and psychological parameters of patients with gingivitis. Materials and methods: Patients were randomly assigned into four conditions: IOC, TM, IOC + TM and control, and examined at three assessment points over eight months (N = 142). Bleeding on marginal probing (BOMP), dental hygiene (brushing and flossing) and social cognitive determinants of behaviour change (outcome expectancies, action and volitional self‐efficacy, intention, planning and action control) were evaluated in an examiner‐blind controlled study. Mixed‐effects modelling was employed to examine changes in study outcomes. Mediations by the psychological determinants were inspected for the effect on treatment groups in clinical parameters and behaviour. Results: Compared to the control group, all treatment conditions improved dental hygiene and revealed a significant decrease in BOMP from baseline to 4 months, maintained at 8 months; this was clinically relevant in the IOC + TM group, where individuals had more positive outcome expectancies as well as higher levels of action self‐efficacy and intention from baseline to four months, maintained at eight months. Volitional self‐efficacy was reinforced in all treatments. The psychological determinants did not prove to be the mechanisms responsible for these effects. Conclusions: A multiple‐strategy benefit from using the IOC in consultation and TM between appointments improves clinical, behavioural and psychological parameters of periodontal health four months after treatment, maintained at eight months’ follow‐up. Insights are provided for the efficacy of the images and text messages for oral hygiene changes.